Production Planning of Cassava Chips in Small Home Business - Rohmatin, Yuyun Yuniar; Wahyuni, Rossi Septy; Raharja, Mei; Fauzia, Siva (Universitas Negeri Jakarta, 2025)
The production process of cassava chips begins with the preparation of cassava raw materials and then the process of separating the skin from cassava. The process of cutting cassava into a certain size uses a special machine that is operated manually. The process of frying cassava using a large pan and the process of packaging into plastic are the last step of production. Planning the production of cassava chips starts with preparing the needs of raw materials for production for 3 days in a week ordered from 3 different suppliers to prepare production needs, the quantity needed in purchasing from suppliers includes 120 kg of cassava, 9 kg of red chili, 1 kg of garlic, 3 kg of lime, 27 kg of cooking oil, 9 kg of sugar and 0.25 kg of salt. The initial supply of cassava raw materials provided is 120 kg and at the end of the week the production inventory needs are 80 kg left from the use of 40 kg at the end of the week for the next production.